Falou AI In pronunciation practice: insights from students’ experiences - Ramdhani, Nia; Hilmawan, Lana Givan; Saqinah, Rizky Febriyanti; Ariawan, Soni; Suhandra, Ika Rama (Mell Baou Publisher, 2025)
This research intends to study students' viewpoints on the Falou application as a tool in improving EFL students' English pronunciation skills at the State Islamic University of Mataram. The data were collected through interviews, observation, and documentation from 10 students who are in different semesters and are applied investigatively through a descriptive qualitative approach. Findings reveal that out of most students, the result is positive feedback concerning the Falou application because they are motivated by the fact that it is easy to access, real-time, and interactive with easy measuring pronouncing correctness and self-confidence in speaking with them. Other challenges are limited feature access, random AI misrecognition, and distracting advertisements. The present study discusses possibilities for the Falou application used as an effective supplementary mechanism for English language learning pronunciation practice.